Wilms' Tumour 1 (WT1) peptide vaccination in patients with acute myeloid leukaemia induces short‐lived WT1‐specific immune responses. (16th November 2013) - Uttenthal, Benjamin; Martinez‐Davila, Irma; Ivey, Adam; Craddock, Charles; Chen, Frederick; Virchis, Andras; Kottaridis, Panagiotis; Grimwade, David; Khwaja, Asim; Stauss, Hans; Morris, Emma C.
Summary Wilms' Tumour 1 (WT1) is a zinc finger transcription factor that is over‐expressed in acute myeloid leukaemia (AML). Its restricted expression in normal tissues makes it a promising target for novel immunotherapies aiming to accentuate the cytotoxic T lymphocyte (CTL) response against AML. Here we report a phase I/II clinical trial of subcutaneous peptide vaccination with two separate HLA‐A2‐binding peptide epitopes derived from WT1, together with a pan‐DR binding peptide epitope (PADRE), in Montanide adjuvant. Eight HLA‐A2‐positive patients with poor risk AML received five vaccination cycles at 3‐weekly intervals. The three cohorts received 0·3, 0·6 and 1 mg of each peptide, respectively. In six patients, WT1‐specific CTL responses were detected using enzyme‐linked immunosorbent spot assays and pWT126/HLA‐A*0201 tetramer staining, after ex vivo stimulation with the relevant WT1 peptides. However, re‐stimulation of these WT1‐specific T cells failed to elicit secondary expansion in all four patients tested, suggesting that the WT1‐specific CD8+ T cells generated following vaccination may be functionally impaired. No correlation was observed between peptide dose, cellular immune response, reduction in WT1 mRNA expression and clinical response. Larger studies are indicated to confirm these findings.